Role of miR‐200 family members in survival of colorectal cancer patients treated with fluoropyrimidines. Issue 7 (10th February 2014) - Diaz, Tania; Tejero, Rut; Moreno, Isabel; Ferrer, Gerardo; Cordeiro, Anna; Artells, Rosa; Navarro, Alfons; Hernandez, Raquel; Tapia, Gustavo; Monzo, Mariano
<x xml:space="preserve">Abstract</x> Background and Objectives Surgery is the standard treatment for colorectal cancer (CRC), and adjuvant chemotherapy has been shown to be effective in stage III but less so in stage II. We have analyzed the expression of the miR‐200 family in tissue samples from resected CRC patients and correlated our findings with survival to adjuvant treatment with fluoropyrimidines. Methods Tumor tissue samples were obtained from 127 surgically resected patients with stage I–III CRC. miRNA detection was performed using TaqMan MicroRNA assays. Results High levels of miR‐200a and miR‐200c were associated with longer overall survival, while high levels of miR‐429 correlated with longer overall and disease‐free survival (DFS). In the subgroup of 56 patients treated with fluoropyrimidines and in the smaller subgroup of 32 stage II patients treated with fluoropyrimidines, those with high levels of miR‐200a, miR‐200c, miR‐141, or miR‐429 had significantly longer overall and DFS. Low miR‐429 levels were identified as an independent prognostic marker. High levels of miR‐429 combined with 5‐fluorouracil inhibited cell invasion in LOVO cells. Conclusions miR‐200a, miR‐200c, miR‐141, and miR‐429 expression levels may identify CRC patients, including those with stage II disease, who are most likely to benefit from adjuvant chemotherapy. J. Surg. Oncol 2014; 109:676–683. © 2014 Wiley Periodicals, Inc.